Pengaruh Biji Kecubung (Datura Metel) Sebagai Bioinsektisida terhadap Mortalitas Kecoa Amerika (Periplaneta Americana) - Riski Priwahyuni; Yunita Wardianti; Sepriyaningsih Sepriyaningsih (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to determine the effect of amethyst seeds (Datura metel) as a bioinsecticide on the mortality of American cockroaches (Periplaneta americana). This study uses a completely randomized design (CRD) with 5 treatments and 5 replications. The treatments are P0 0% bioinsecticide level, P1 baygon, P2 10%, P3 20%, P4 30%, and P5 40%. This research was conducted at the STKIP-PGRI Lubuklinggau Laboratory. The materials used in this study are old amethyst seeds, American cockroaches, water and baygon. Data collection was carried out by observation technique which was carried out in the first 4 hours of observation for 24 hours until the third day after treatment, then counted the number of dead cockroaches. Data analysis techniques with steps namely normality test, homogeneity test, Anava test and BNJ advanced test. Based on the calculation of the Anava Test one path can be calculated F (5,450)> F table (2.74) showed very significant results (α = 0.05). The results showed that there was an effect of amethyst seeds (Datura metel) as bioinsecticide on the mortality of American cockroaches (Periplaneta americana). In BNJ advanced test calculations, the concentration of 40% is significantly different from the concentrations of 10%, 20%, 30% and 0%. The optimum concentration of mortality of American cockroaches in the cone seeds at a concentration of 40%. Conclusion, there is a significant effect of amethyst seeds (Datura metel) as bioinsecticide on the mortality of American cockroaches (Periplaneta americana). Keywords: Bioinsecticide, Amethyst Seeds (Datura metel), Mortality, American Cockroach (Periplaneta americana)